Real-time implementation of the high-fidelity NBI code RABBIT into the discharge control system of ASDEX Upgrade. (1st June 2023) - Weiland, M.; Bilato, R.; Sieglin, B.; Felici, F.; Giannone, L.; Kudlacek, O.; Rampp, M.; Scheffer, M.; Treutterer, W.; Zehetbauer, T.; ,; ,
Abstract: For the first time, a real-time capable NBI code, which has a comparable fidelity to the much more computationally expensive Monte Carlo codes such as NUBEAM, has been coupled to the discharge control system of a tokamak. This implementation has been done at ASDEX Upgrade and is presented in this paper. Modifications to the numerical scheme of RABBIT for the time-dependent solution of the Fokker–Planck equation have been carried out to make it compatible with the non-equidistant time-steps, as they occur in real-time simulations. We demonstrate that this allows RABBIT to run in real-time both in a steady-state and time-dependent fashion and show and discuss an actual real-time simulation. Its accuracy is identified by comparing to offline RABBIT and TRANSP-NUBEAM runs (where more diagnostics are available for preciser inputs).